SOCIAL COGNITIVE CAREER THEORY AND THE GOAL OF BECOMING A CERTIFIED PUBLIC ACCOUNTANT IN PUBLIC ACCOUNTING FIRM EMPLOYEES - Sharon Anastasya Mongkar; Anak Agung Gde Putu Widanaputra (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research is motivated by the phenomenon of declining interest in the certified public accounting profession in Indonesia, even though this profession offers many career opportunities. This study aims to examine the influence of social cognitive career theory on the goal of becoming a certified public accountant, with a focus on self-efficacy variables and outcome expectations. The research method used purposive sampling to select a sample of public accounting firm employees, with a total of 100 respondents. However, there were 10 incomplete questionnaires so that 90 respondents were used. The data analysis technique used is multiple linear regression. The research results show that self-efficacy and outcome expectations have a significant positive influence on the goal of becoming a certified public accountant. The conclusions of this study confirm that the higher a person's self-efficacy and outcome expectations, the more likely they are to pursue CPA certification. The implication of the results of this research is the importance of strengthening self- efficacy and outcome expectations in individuals through various education and training strategies, in order to increase interest and commitment to the certified public accounting profession in Indonesia. The practical implications of this research provide material for consideration to help educational institutions and accounting training institutions in developing more effective programs to prepare participants to achieve the Certified Public Accountant (CPA) title, with a focus on increasing self-efficacy and outcome expectations.